The World Experience in the Regulation of the Land Circulation - Kaletnik, Grygorii; Honcharuk, Inna; Yemchyk, Tetiana; Okhota, Yuliia (European Journal of Sustainable Development, 2020)
The article examines the state of the agricultural development in Ukraine in the context of the crop and livestock industries. The use of land resources by different owners and the structure of agricultural land were also analyzed. The problems of the development of the electronic cadastre of the land resources were identified. The proposals to use the world experience of agricultural land use in Ukraine were substantiated. The proposals for the improvement the legal framework in the field of the agricultural land circulation were elaborated. Keywords: land market, gross production, world experience, crop production, animal husbandry, land resources